Recent Advances on Anti-interference Control Strategies for Better Operation - Gao, Bingwei; Ye, Yongtai; Guan, Hao; Sheng, Wei (Recent Patents on Engineering, 2023)
Background: Under the influence of complex external environment and the internal parameter perturbation of the system itself, many interference problems hinder the development of the controlled object according to the predetermined trajectory. Objective: The objective of this study is to provide the corresponding anti-interference control methods for different degrees of interference and introduce their respective characteristics. Methods: This paper mainly summarizes the application examples of anti-interference control algorithms in the face of different interference problems, which are mainly divided into three categories. Especially two new concepts, whose names are composite anti-interference control and innovative anti-interference control algorithm design, are presented. At the same time, this paper not only summarizes the outstanding contribution of anti-interference control in the mechanical field, but also expounds on the application examples of coupling of anti-interference control in electrical aspect and describes the application of anti-interference control in other planets. Results: From the interference problem on the earth to the anti-interference control of outer space, the control algorithm shows the unique charm step by step. In the future, to cope with the complex and changeable environment, the anti-interference algorithm will continue to be optimized in depth, letting the control system run steadily in direction of fast, accurate and stable on the expected track. Conclusion: Anti-interference control plays an important practical role in the control of systems. Whether in the mechanical field or coupling in other aspects such as electrical, it can help the system run better according to the needs of the controller. It is effective and reasonable to combine different strategies for the systems, so that the systems are more accurate and stable.
Keywords: innovative anti-interference control